Upaya Membudayakan Kepemimpinan Transformasional di Lembaga Pendidikan Islam - Yuni Masrifatin (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
Leaders who have far-reaching thoughts, have a strong vision and mission will be able to break the organization into the forefront. Some theories about the model and leadership style offered, all have their strengths and weaknesses, adjusted to the conditions or conditions of the institution being managed. A leader is said to be transformational in style if it can change the situation, change what is usually done, talk about noble goals, have a reference to the values ​​of freedom, justice and equality. In this article, we will discuss efforts to cultivate transformational leadership in educational institutions. Some things that must be cultivated are (1) expressing a clear and interesting vision and building a commitment to a new vision. (2) explain how the vision can be achieved (3) act as leaders who understand, motivate, delegate and inspire, and are broad-minded.